'Climate refugees - The world's forgotten victims' an exploration of international refugee protection in the context of climate change related cross border displacement - Yasmine Luhandjula (University of Pretoria, 2025)
Mini Dissertation (LLM (International Law))--University of Pretoria, 2025.